MANAJEMEN PEMANFAATAN MEDIA PEMBELAJARAN AUDIO VISUAL DALAM MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM - Danang Dwi Prasetyo; Qomarudin; Syarif Hidayat; Diningrum Citraningsih (STAI Sangatta Kutai Timur, 2022)
This research is motivated by the lack of use of learning media and the saturation of students when studying and student learning outcomes that have not been maximized. This study aims to determine the use of audio-visual learning media for SKI subjects in class XI MAN 03 Bantul Yogyakarta. The research method used is a quasi-experimental method. This method was chosen because the purpose of the study was to determine the effect that arises from a treatment, namely the implementation of Islamic Cultural History learning using audio-visual media which was applied to the experimental group compared to the control group who studied Islamic Cultural History without using audio-visual media. Data collection is done by giving interviews, observations, documentation, and tests. Sources of data obtained from SKI teachers and students in class XI.Management of the use of audio-visual media at MAN 03 Bantul Yogyakarta is done by means of teachers planning learning by preparing an implementation plan for the learning process according to the curriculum, including materials, supporting tools, and evaluation tools. In the learning process, the teacher observes student attitudes and evaluates them. The implementation of this audio-video learning media is very helpful for teachers in increasing student interest and enthusiasm. It can be proven that student learning outcomes in the experimental class using audiovisuals are superior to those in the control class who are not given special treatment, it can be seen from the average results. The posttest score of the experimental class students is 87.10 with a total score of 2700. Meanwhile, the control class average is 71.29 with a total score of 2210.